Synthesis and properties of glass-forming 2-substituted perimidines. (21st November 2016) - Butkute, Rita; Lygaitis, Ramunas; Gudeika, Dalius; Grazulevicius, Juozas V.; Obushak, Mykola D.
ABSTRACT: 2-Substituted perimidine derivatives were synthesized by condensation of 1, 8-diaminonaphthalene and the different formyl derivatives. Alkylation of the intermediate compounds was performed using microwave irradiation using potassium and cesium carbonate as a base. The synthesized compounds were characterised by UV and luminescence spectroscopies, cyclic voltammetry, thermogravimetry, differential scanning calorimetry. They exhibit relatively high thermal stability with the temperatures of the onset of thermal degradation ranging from 230 to 392°C. Most of the synthesized perimidines are capabale to form glasses with glass transition temperatures up to 197°C. The alkyl group attached to the perimidinyl moiety influences the conformation of the molecules and consequently the absorption and emission spectra. The values of ionization potential of the layers of the synthesized derivatives range from 5.26 to 5.52 eV.